Transnational and Local Tariqa: Spread and Political Attitudes - Muhammad Ichsan Rifqi (University of Darussalam Gontor, Indonesia, 2025)
This article aims to examine Sufi orders as both transnational and local movements, focusing on the interactions between local and transnational orders and their strategies in shaping political stances in the countries where their teachings are propagated. The study employs a qualitative method with a library research approach. The findings indicate that the dissemination of Sufi groups occurs through various channels, including proselytization, trade, diaspora migration, and the utilization of digital technology. In determining their political positions, Sufi groups consider three main factors: (1) resistance to colonialism, (2) the protection of Sufi identity when they are a minority, often relying on state support and policies, particularly amid rising Islamic orthodoxy, and (3) responses to threats from radical groups. Initially traditional and individualistic, these orders have transformed into a form of neo-Sufism that balances worldly and spiritual concerns, thereby enabling participation in both local and global politics. The study provides nuanced insights into the adaptability and global role of Sufi orders, highlighting their capacity to navigate diverse socio-cultural contexts, build transnational networks, and contribute to interfaith and sustainable community dialogue. These findings provide valuable insights into the resilience of Sufi movements and their potential contributions to addressing contemporary global challenges.